Let's be physically active for life: preventive actions to ensure good health when becoming old - Aldís Gunnarsdóttir 1992- (2017)
Whether you are 20 or 60 years old it makes no difference, physical activity will always be vital for your health. Over the past century, awareness of physical health has increased and health promoting strategies have advanced and become more numerous. Perception of the word “prevention’’ has developed and the idea of good health in the evening of life has become more considered. People are expected to live longer than they did a hundred years ago which has its pros and cons. A longer life brings us no benefits if life is just a constant struggle. Life should be worth living. People should be in control of how their body develops as they age and not pertain subdued to the effects of aging. Age should also not be a determinant factor for opportunities of physical activity. This narrative is a way of evaluating today’s status of physical activity among the elderly in Iceland and to put forth ideas on how to improve it. Key words: Physical activity, aging, elderly, motivate